Transformation Of Nutritional Literacy Culture In Deep Learning Of Students With Hearing Impairment Through Demonstration Video Media - Devira Putri Giana; Reza Akbar Fauzan; She Fira Azka Arifin (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
Students with hearing impairment in Special Schools (SLB) face limited access to accessible nutritional information media, making them vulnerable to Ultra-Processed Food (UPF) consumption patterns in their daily school meals. This study aims to examine the effectiveness of demonstration video media in transforming nutritional literacy culture and reducing UPF consumption among students with hearing impairment using a Deep Learning approach. The method used was Mixed Methods Research with an Explanatory Sequential design, combining Action Research and Case Study. Research subjects were 6 hearing-impaired seventh-grade students at SLB Aisyiyah Tulangan, Sidoarjo. Data were collected through a Visual Nutritional Literacy Test (pre-post test), a 14-day Daily Food Audit, and parent interviews based on the 8 Graduate Profile Dimensions. Results showed an increase in nutritional literacy scores from an average of 3.2 to 7.1 (scale of 8), and a shift in school meals from UPF dominance (100%) to green vegetable-based meals (83%) following a two-week intervention. Qualitative analysis revealed the emergence of agency, critical thinking, and triadic teacher-student-parent collaboration as manifestations of Deep Learning. Demonstration video media proved effective as a cognitive bridge in facilitating sustainable nutritional behavior transformation among students with hearing impairment.